A cotransformation system of the unicellular red alga Cyanidioschyzon merolae with blasticidin S deaminase and chloramphenicol acetyltransferase selectable markers - Takayuki Fujiwara; Shunsuke Hirooka; Shin-ya Miyagishima (BMC Plant Biology, 2021)
Abstract Background The unicellular red alga Cyanidioschyzon merolae exhibits a very simple cellular and genomic architecture. In addition, procedures for genetic modifications, such as gene targeting by homologous recombination and inducible/repressible gene expression, have been developed. However, only two markers for selecting transformants, uracil synthase (URA) and chloramphenicol acetyltransferase (CAT), are available in this alga. Therefore, manipulation of two or more different chromosomal loci in the same strain in C. merolae is limited. Results This study developed a nuclear targeting and transformant selection system using an antibiotics blasticidin S (BS) and the BS deaminase (BSD) selectable marker by homologous recombination in C. merolae. In addition, this study has succeeded in simultaneously modifying two different chromosomal loci by a single-step cotransformation based on the combination of BSD and CAT selectable markers. A C. merolae strain that expresses mitochondrion-targeted mSCARLET (with the BSD marker) and mVENUS (with the CAT marker) from different chromosomal loci was generated with this procedure. Conclusions The newly developed BSD selectable marker enables an additional genetic modification to the already generated C. merolae transformants based on the URA or CAT system. Furthermore, the cotransformation system facilitates multiple genetic modifications. These methods and the simple nature of the C. merolae cellular and genomic architecture will facilitate studies on several phenomena common to photosynthetic eukaryotes.